Transient Synchronization Stability Modeling and Analysis of Grid-Following Converter Considering Current Dynamics - Teklu Dereje; Ling Zhan; Bin Hu; Heng Nian (IEEE Access)
The increasing integration of converter-based energy sources, in the modern power grid has brought a significant challenge in the form of transient instability of grid-following converters (GFCs). Existing research on transient stability merely centered on phase looked loop (PLL) dynamics while the current control loop is ignored. However, in the scenario of a high power GFC connected with weak grid, it is not possible to approximate the current loop dynamics as a unit gain, since the low switching frequency of high-power converters does not allow for high current loop bandwidth. This paper finds that slow current dynamics together with the weak grid’s characteristics might deteriorate the transient stability of GFC when the system is subjected to a shallow grid voltage drop. Accordingly, a sixth-order nonlinear model is proposed to describe the coupling effect between the current loop and PLL. The accuracy of the model is confirmed through time-domain simulation and parameter sensitivity analysis is performed. Finally, theoretical analysis is validated through experimental tests.